MicroRNA expression profiling of human blood monocyte subsets highlights functional differences. Issue 3 (July 2015) - Dang, Truong‐Minh; Wong, Wing‐Cheong; Ong, Siew‐Min; Li, Peng; Lum, Josephine; Chen, Jinmiao; Poidinger, Michael; Zolezzi, Francesca; Wong, Siew‐Cheng
Summary Within human blood there are two subsets of monocytes that can be identified by differential expression of CD16. Although numerous phenotypic and functional differences between the subsets have been described, little is known of the mechanisms underlying the distinctive properties of the two subsets. MicroRNAs (miRNAs) are small non‐coding RNAs that can regulate gene expression through promoting mRNA degradation or repressing translation, leading to alterations in cellular processes. Their potential influence on the functions of monocyte subsets has not been investigated. In this study, we employed microarray analysis to define the miRNA expression profile of human monocyte subsets. We identified 66 miRNAs that were differentially expressed (DE) between CD16+ and CD16− monocytes. Gene ontology analysis revealed that the predicted targets of the DE miRNAs were predominantly associated with cell death and cellular movement. We validated the functional impacts of selected DE miRNAs in CD16− monocytes, over‐expression of miR‐432 significantly increases apoptosis, and inhibiting miR‐19a significantly reduces cell motility. Furthermore, we found that miR‐345, another DE miRNA directly targets the transcription factor RelA in monocytes, which resulted in the differential expression of RelA in monocyte subsets. This implicates miR‐345 indirect regulation of many genes downstream of RelA, including important inflammatory mediators. Together, our data show that DE miRNAs could contribute substantially to regulating the functions of human blood monocytes.